2019
DOI: 10.1021/jacs.9b05009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of C4-Aminated Indoles via a Catellani and Retro-Diels–Alder Strategy

Abstract: Highly functionalized 4-aminoindoles were synthesized via the three-component cross-coupling of o-iodoaniline, N-benzoyloxyamines, and norbornadiene. The Catellani and retro-Diels–Alder strategy was used in this domino process. o-Iodoaniline, with electron-donating and sterically hindered protecting groups, made the reaction selective toward o-C–H amination. On the basis of density functional theory calculations, the intramolecular Buchwald coupling of this reaction underwent a dearomatization and a 1,3-pallad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 81 publications
2
28
0
Order By: Relevance
“…[10] In 2019, Liang et al elegantly developed palladium catalyzed method for the synthesis of highly functionalized 4aminoindoles 16 from three-component cross coupling of ortho-iodoaniline 13, N-benzoyloxyamines 14, and norbornadiene 15 (Scheme 3). [11] Optimization studies revealed that use of Pd(OAc) 2 (10 mol%) as the catalyst, PPh 3 (20 mol%) as the ligand and Cs 2 CO 3 (4 equiv) as a base in toluene at 140 0 C for 36 h. In this reaction, strong electron withdrawing groups such as À NO 2 , À F and À Cl containing ortho-iodoanilines worked well and provided the desired products in excellent yields. The method was also found to be feasible for heterocyclic substrates such as 3iodopyridin-2-amine and 4-amino-7-azaindole afforded the corresponding products in good yields.…”
Section: Indole Synthesismentioning
confidence: 97%
See 1 more Smart Citation
“…[10] In 2019, Liang et al elegantly developed palladium catalyzed method for the synthesis of highly functionalized 4aminoindoles 16 from three-component cross coupling of ortho-iodoaniline 13, N-benzoyloxyamines 14, and norbornadiene 15 (Scheme 3). [11] Optimization studies revealed that use of Pd(OAc) 2 (10 mol%) as the catalyst, PPh 3 (20 mol%) as the ligand and Cs 2 CO 3 (4 equiv) as a base in toluene at 140 0 C for 36 h. In this reaction, strong electron withdrawing groups such as À NO 2 , À F and À Cl containing ortho-iodoanilines worked well and provided the desired products in excellent yields. The method was also found to be feasible for heterocyclic substrates such as 3iodopyridin-2-amine and 4-amino-7-azaindole afforded the corresponding products in good yields.…”
Section: Indole Synthesismentioning
confidence: 97%
“…elegantly developed palladium catalyzed method for the synthesis of highly functionalized 4‐aminoindoles 16 from three‐component cross coupling of ortho ‐iodoaniline 13 , N ‐benzoyloxyamines 14 , and norbornadiene 15 (Scheme 3). [11] …”
Section: Synthesis Of Nitrogen Containing Heterocyclesmentioning
confidence: 99%
“…In 2019, Liang demonstrated such a strategy was compatible for the one‐step synthesis of highly functionalized 4‐aminoindoles 91 by combing o ‐iodoanilines with N‐ benzoyloxyamines (Scheme 35). [ 96 ] Importantly, electron‐donating group with large steric bulkiness on the nitrogen proved to be more beneficial, and the Catellani and retro‐Diels−Alder reactions could occur at the same time, thus enabling the one‐pot synthesis of 4‐aminoindoles.…”
Section: Typical Catellani Reactionsmentioning
confidence: 99%
“…If so, it would lead to highly valuable 1,2,3‐trifunctionalized arenes by the direct trifunctionalization of ortho ‐unsubstituted aryl halides at their three adjacent positions. [ 34‐38 ] However, the development of such a reaction is not a trivial task. According to the reactivity difference of electrophiles E a and E b that are involved, two main reaction modes could be envisioned.…”
Section: Background and Originality Contentmentioning
confidence: 99%